A Fluid Flow Modelling Approach to Gold Exploration in the Hodgkinson Province, Far North Queensland - W Gorczyk; S Corbel; P J. T Donchak (The Australasian Institute of Mining and Metallurgy, 2008)
The Hodgkinson Province numerical modelling project aims to develop an improved understanding of the physical conditions that lead to the localisation of goldbearing fluids within known systems and apply this understanding to the prediction of potential new sites of gold mineralisation. The project follows a series of stages from identifying the key parameters required to construct and test simulations through to reverse engineering of known deposits and ultimately applying the conditions identified in the preliminary stages to predictive simulations. Results of the modelling demonstrate strong geometric controls of the localisation of fluids during mineralisation. An EXTENDED ABSTRACT is available for download. A full-length paper was not prepared for this presentation.